Attending Walimatul ‘Ursy : Pregnant Women Due To Adultery Perspectif Islamic Law - Afroo, Fakhriyah Annisa; Julir, Nenan; Syelvita, Rema (Jurnal Kawakib, 2024)
The issue being studied is how Islamic law is reviewed when attending Walimatul 'Ursy for women who become pregnant as a result of adultery. The aim of this research is to find out how the law applies to attending walimatul 'ursy for pregnant women due to adultery. To uncover this problem, it was carried out in depth and comprehensively, the research used the library research method (library study), where in this case the author collected data from existing books, articles, scientific works. its relevance to the problem. From the results of this research, it was found that the law of marrying a woman who is pregnant as a result of adultery is mubah (permissible) if the person who marries the woman who is pregnant as a result of adultery is the man who impregnated her. A good walimatul 'ursy according to Islamic law is a wedding walimah where there is no immorality or immorality in the implementation of the party and the law of attending a walimatul 'ursy for a woman who is pregnant as a result of adultery is permissible as long as there is no immorality or immorality in the walimatul 'ursy.